2005
DOI: 10.1007/s00426-004-0212-7
|View full text |Cite
|
Sign up to set email alerts
|

Organization of visuo-spatial serial memory: interaction of temporal order with spatial and temporal grouping

Abstract: This study investigates whether memory for sequences of spatial locations can be represented hierarchically, that is, as successive groups containing the order of constituent locations. Two grouping manipulations are used: Temporal grouping, based on the verbal serial memory literature, and spatial grouping, based on recent empirical work on visuo-spatial serial memory. In Experiment 1, we examine the relationship between spatial grouping and temporal order and showed that recall performance increases when bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
72
0
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(103 citation statements)
references
References 77 publications
21
72
0
10
Order By: Relevance
“…Participants may be internally representing temporal proximity as spatial proximity, (Boroditsky, 2000). This finding is consistent with those of Parmentier et al (2006) who also reported hierarchical organisation of visuospatial items as a result of temporal grouping at presentation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Participants may be internally representing temporal proximity as spatial proximity, (Boroditsky, 2000). This finding is consistent with those of Parmentier et al (2006) who also reported hierarchical organisation of visuospatial items as a result of temporal grouping at presentation.…”
Section: Discussionsupporting
confidence: 81%
“…The benefit of temporal grouping during verbal plus visual presentation experienced by those with DS may involve spatially differentiating the visual items when they are presented within a temporally grouped schedule, but not necessarily with the two items in the form of an interaction. Parmentier, et al (2006), explored the effect of temporal grouping upon typically developing adult participants' visuospatial serial recall performance, and found that temporally grouped presentation alone (Exp 4) was sufficient to result in memory recall benefits in the visual domain. Specifically, the migration of visuospatial items between groups at recall was decreased as a result of temporal grouping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, similar serial position curves with recency and primacy effects are observed in serial recall of verbal and spatial sequences (Avons, 1998;Jones, Farrand, Stuart, & Morris, 1995). Other phenomena such as the disruptive effect of to-be-ignored stimuli including irrelevant sound stimuli (Jones et al, 1995) and suffixes (Parmentier, Tremblay, & Jones, 2004), the beneficial effect of temporal grouping (Parmentier, Andrés, Elford, & Jones, 2006), and Hebb list repetition (Couture & Tremblay, 2006;Turcotte, Gagnon, & Poirier, 2005) have been demonstrated in spatial as well as verbal serial recall. Such evidence of functional equivalence has led some investigators to posit a single mechanism for verbal and spatial memory (e.g., Jones et al, 1995) and others to propose distinct mechanisms but those that follow similar general principles (Logie, 1995).…”
mentioning
confidence: 79%
“…Nos estudos de Kemps (2001) a capacidade de recordação de sequências espaciais foi determinada pela redundância de cada sequência. A proximidade temporal ou espacial das posições facilita a recordação de sequências (Farrand et al, 2001;Parmentier et al, 2006). Rossi-Arnaud et al (2006) sugerem que o executivo central pode estar envolvido tanto na codificação como no armazenamento das sequências espaciais, independentemente de essas sequências serem redundantes ou não.…”
Section: Memória Espacialunclassified